2007
DOI: 10.1677/jme-07-0043
|View full text |Cite
|
Sign up to set email alerts
|

Role of specificity protein transcription factors in estrogen-induced gene expression in MCF-7 breast cancer cells

Abstract: Deletion analysis of several 17b-estradiol (E 2 )-responsive genes have identified GC-rich sites that are associated with hormone-induced transactivation in MCF-7 breast cancer cells. However, the role of individual specificity proteins (Sps) in mediating hormone-induced gene expression has not been unequivocally determined. In transient transfection studies using E 2 -responsive GC-rich promoters from the E 2 F1, carbamoylphosphate synthetase/aspartate transcarbamylase/dihydroorotase (CAD), and retinoic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 77 publications
3
25
0
Order By: Relevance
“…We found Sp3, but not Sp1, to be the major Sp protein activating the TFF1 upstream promoter region in response to E2 (Sun et al, 2005). This was supported by other studies where it was shown that Sp3 plays a major role in ER /Sp-mediated gene expression in MCF-7 cells (Khan et al, 2007). In general, Sp1 usually activates transcription and Sp3 represses or most weakly activates transcription (Higgins et al, 2006;Jaiswal et al, 2006;Noe et al, 2001).…”
Section: Role Of Transcription Factors Sp1 and Sp3 In Breast Cancersupporting
confidence: 86%
See 1 more Smart Citation
“…We found Sp3, but not Sp1, to be the major Sp protein activating the TFF1 upstream promoter region in response to E2 (Sun et al, 2005). This was supported by other studies where it was shown that Sp3 plays a major role in ER /Sp-mediated gene expression in MCF-7 cells (Khan et al, 2007). In general, Sp1 usually activates transcription and Sp3 represses or most weakly activates transcription (Higgins et al, 2006;Jaiswal et al, 2006;Noe et al, 2001).…”
Section: Role Of Transcription Factors Sp1 and Sp3 In Breast Cancersupporting
confidence: 86%
“…In case of the p21 Waf1/Cip1 promoter, we also observed a lower Sp3 association in response to estrogen stimulation in MCF-7 cells (Mandal and Davie, 2007). We demonstrated that both Sp1 and Sp3 associated with TFF1, but Sp3, not Sp1, plays a major role in the estrogen activated ER /Sp-mediated gene expression in MCF-7 cells (Khan et al, 2007;Li and Davie, 2008). Therefore, in the context of estrogen stimulation, Sp1 and Sp3 play dual roles in regulating gene expression.…”
Section: A Comparative Analysis Of Sp1-sp3 Interactions In Er+ and Ermentioning
confidence: 55%
“…The combined knockdown of Sp1, Sp3, and Sp4 (iSp) was the most effective treatment for decreasing p65 and p50 protein expression in L3.6pL cells. The differential effect of Sp1, Sp3, and Sp4 on regulation of other genes has also previously been reported in different cancer cell lines (22,(33)(34)(35). In addition, Sp knockdown also inhibited Panc28 and L3.6pL cell growth and induced PARP cleavage, indicating , and effects on Sp proteins, and p65 and p50 subunits of NFB were determined by Western blot analysis as described under "Experimental Procedures."…”
Section: Curcumin Decreases Sp Transcription Factors and Sp-dependentmentioning
confidence: 52%
“…Non-RARE regions located between proximal and distal RAREs, which contain several SP1 and SP3 sites appear to play an important role in the basal promoter activity in HEK293T cells only, but in response to at-RA in both cell types. These transcriptional factors have been shown to interact with RARs in driving the expression of several genes in response to RA (Wolf et al, 2005; Khan et al, 2007; Laliotis et al, 2007; Islam et al, 2008; Zolfaghari and Ross, 2009). …”
Section: Discussionmentioning
confidence: 99%